2005
DOI: 10.1039/b414241a
|View full text |Cite
|
Sign up to set email alerts
|

Polycationic dendrimers interact with RNA molecules: polyamine dendrimers inhibit the catalytic activity of Candida ribozymes

Abstract: Various polyamine dendrimers with a triethanolamine core inhibit the activity of the Candida ribozyme by forming RNA-dendrimer complexes via electrostatic interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 13 publications
4
74
0
Order By: Relevance
“…Owing to the ease of synthesis and commercial availability, PAMAM dendrimers are among the most utilized dendrimer-based vectors for gene transfer. [40] Notably, it has been shown recently that PAMAMs possess strong binding affinity for RNA molecules, [41,42] interact tightly with group I intron ribozymes, [41] and, last but not least, can efficiently deliver siRNA and thus induce gene silencing in cell cultures. [43] Notwithstanding these perspectives, relatively few attempts have been made so far along these lines to study in detail the molecular mechanisms underlying the complexa- Figure 12.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the ease of synthesis and commercial availability, PAMAM dendrimers are among the most utilized dendrimer-based vectors for gene transfer. [40] Notably, it has been shown recently that PAMAMs possess strong binding affinity for RNA molecules, [41,42] interact tightly with group I intron ribozymes, [41] and, last but not least, can efficiently deliver siRNA and thus induce gene silencing in cell cultures. [43] Notwithstanding these perspectives, relatively few attempts have been made so far along these lines to study in detail the molecular mechanisms underlying the complexa- Figure 12.…”
Section: Resultsmentioning
confidence: 99%
“…Poly(amidoamine) or PAMAM dendrimers consist of polyamide branches stemming from a central ammine or diaminoalkane core (see Fig. 1 [10][11][12][13][14], whereas the half generation dendrimers have multiple anionic charges which are ideal for cationic drugs or for reversible coordination to platinum complexes [15]. PAMAM dendrimers of generations 1 to 10 are nanometre in diameter, and thus, ideal for targeting tumours through the EPR effect.…”
Section: Introductionmentioning
confidence: 99%
“…Dendrimers (Scheme 1) are also unique synthetic macromolecules of nanometer dimensions with a highly branched structure and globular shape with strong affinity towards DNA and RNA complexation [4][5][6][7][8][9][10]. It has been shown that synthetic polymers induce significant changes in DNA and RNA solubility and structure under given conditions [8][9][10][11][12][13][14][15][16][17][18][19][20]. Synthetic polymers are also used to transport miRNA and siRNA in vitro [11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that synthetic polymers induce significant changes in DNA and RNA solubility and structure under given conditions [8][9][10][11][12][13][14][15][16][17][18][19][20]. Synthetic polymers are also used to transport miRNA and siRNA in vitro [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. PEGylation of synthetic polymers such as dendrimers is shown to reduce toxicity and increase biocompatibility and DNA Transfection [6,7,9].…”
Section: Introductionmentioning
confidence: 99%